2022
DOI: 10.3991/ijim.v16i03.27257
|View full text |Cite
|
Sign up to set email alerts
|

Seamless Learning Model with Enhanced Web-Quizzing in the Higher Education Setting

Abstract: The research studied the effectiveness of a three-stage Seamless Learning Model with Enhanced Web-Quizzing based on the intensive use of sets of quizzes created in different web-based quiz generators. The findings revealed  that continuous testing using diagnostic, formative, benchmark and summative quizzes, administered at the three stages - familiarisation, formation and assessment, applying such features of seamless learning as learning in various contexts, ubiquitous access to digital learning resources an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…What is more, the authors' experience has shown that during the conflict chats may sometimes become the only means of communication between learners and teachers enhancing students' productivity and interaction, motivating them and supporting psychologically as well as providing feedback in the educational process. What is more, we can assume that online quizzes proposed as a primary learning tool by Mykytiuk et al [1] result in the higher achievements of the students as we also used them in our mobile learning and teaching practice but unlike the stated authors, we considered them as an additional tool in the study of the English language. It is necessary to note also that we fully agree with Papadakis et al [41] about the existence of a great number of mobile apps, which are created for learning, but their educational potential is different and not always sufficient.…”
Section: Discussion and Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, the authors' experience has shown that during the conflict chats may sometimes become the only means of communication between learners and teachers enhancing students' productivity and interaction, motivating them and supporting psychologically as well as providing feedback in the educational process. What is more, we can assume that online quizzes proposed as a primary learning tool by Mykytiuk et al [1] result in the higher achievements of the students as we also used them in our mobile learning and teaching practice but unlike the stated authors, we considered them as an additional tool in the study of the English language. It is necessary to note also that we fully agree with Papadakis et al [41] about the existence of a great number of mobile apps, which are created for learning, but their educational potential is different and not always sufficient.…”
Section: Discussion and Limitationmentioning
confidence: 99%
“…Today the potential of telecommunications, information and mobile technologies for educational purposes can hardly be overvalued. It is actively investigated by researchers [1]- [4] and is becoming stable global pedagogical practice. Utilising mobile teaching and learning in addition to traditional forms and methods has already demonstrated increasing students' progress [5].…”
Section: Introductionmentioning
confidence: 99%
“…1) The papers dealing directly with distance education, namely, the teacher's role in distance teaching (Fokin et al, 2017;Mykytiuk et al, 2022), distance learning perspectives (Kalita, 2020;Traxler, 2018), distance form as a means of life-long learning (Kozlova, 2013), distance courses on the basis of different educational platforms (Karelina, 2004;Smirnova & Afanaseva, 2017) and cloud computing (Holubnycha et al, 2019;Melnychuk et al, 2019), distance teaching and learning principles (Khutorsky, 2014;Zelitchenko, 2020), data analysis of main current trends of different countries (Wotto, 2020), research areas in this educational form (Zawacki-Richter, 2009) and others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the continued development of higher vocational education, the country has set greater standards and expectations for English teaching reform. The basic requirements of English teaching emphasize that the talents cultivated by higher vocational education are applied professionals in technology and production [1], [2]. Higher vocational English courses aim to develop students' language skills, particularly students' capacity to utilize English to deal with every day and international business activities, in addition to helping students build a strong linguistic foundation.…”
Section: Introductionmentioning
confidence: 99%